2019
DOI: 10.1080/21650373.2019.1625827
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of commercial superplasticizers for one-part alkali-activated blast-furnace slag mortar

Abstract: Alkali-activated materials are a low-CO2 alternative for Portland cement in construction. However, one major issue in their use is the poor or varying functionality of the currently available commercial superplasticizers. Especially for one-part ("just add water") alkali-activated materials, the number of studies is limited. In this study, one-part alkali-activated mortar was prepared from blast furnace slag by using solid sodium hydroxide as an activator and microsilica as an additional silica source. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 37 publications
2
20
1
Order By: Relevance
“…Additionally, the obtained results of initial setting time in this study are in agreement with initial setting times for cement types in British standards 197-1 [64]. Furthermore, setting times can be easily increased if needed in some applications with the aid of setting retardant agents such as lignosulfonate which was proven as a suitable retarder for one-part AAC in past studies [65]. 3.6 XRD analysis of hydration products XRD analysis was performed on pastes of samples with the highest strength (AAC3, AAC7 and AAC11) at 28 days and for longer ages (at 90 and 180 days), as presented in Fig.…”
Section: Setting Timesupporting
confidence: 85%
“…Additionally, the obtained results of initial setting time in this study are in agreement with initial setting times for cement types in British standards 197-1 [64]. Furthermore, setting times can be easily increased if needed in some applications with the aid of setting retardant agents such as lignosulfonate which was proven as a suitable retarder for one-part AAC in past studies [65]. 3.6 XRD analysis of hydration products XRD analysis was performed on pastes of samples with the highest strength (AAC3, AAC7 and AAC11) at 28 days and for longer ages (at 90 and 180 days), as presented in Fig.…”
Section: Setting Timesupporting
confidence: 85%
“…Over the past years, one-part geopolymers like OPC manufactured by simply adding water have attracted strong interest [ 16 , 17 ]. The production of OPAAB will enhance the commercial viability of the geopolymer and have the ability to considerably reduce CO 2 emissions compared to OPC mixtures [ 2 , 18 ]. In OPAAB, dry blends consisting of aluminosilicate precursors and solid alkaline activators are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the effect of commercial SPs on properties of ‘one-part’ geopolymers are very limited. For instance, Luukkonen et al [36] recently investigated the effect of different SPs on properties of a one-part geopolymer mortar made of slag as the source material, in conjunction of microsilica as an additional silica source, and sodium hydroxide powder as the solid activator. The authors concluded that for the investigated one-part geopolymer formulation lignosulfonate, melamine, and naphthalene-based SPs were more effective than polyacrylate and polycarboxylate-based SPs.…”
Section: Introductionmentioning
confidence: 99%